Alegorismo pagano y alegorismo cristiano en Orígenes. La polémica contra Celso - Ramos-Lisson, Domingo (Antigüedad y Cristianismo, 1990)
It draws our attention the use of allegorisms in the Celsian controversy as a weapon against the Christians. Celso disauthorized the use of the allegory which the christians applied to the Bible considering that this was patrimony of the grek mythology. In his CONTRA CELSUS, Origen demonstrates the impropriety of the celsian attitude on this matter. With impeccable logic he demonstrates why the reasons which Celso proposes to defend the use of allegorisms to explain the greek myths are applicable with still more reason to the Truth revealed in the Holy Scriptures because this is substantially a rhetorical metaphor which in itself is only a simple methos of exposition. Also highlighted in this study are the two viewpoints of each of the opponents, resulting evident the superior coherence and better treatment of the subject which can be observed in the works of Origen in contrast to that of his dialectical adversary.